CONDITIONS FOR EFFICIENCY INCREASE INDEPENDENT WORK OF JUNIOR SCHOOLCHILDREN IN UKRAINIAN LANGUAGE LESSONS - N.I. Bilokonna (Academy of Cognitive and Natural Sciences, 2006)
The article examines the essence of the independent learning on the Ukrainian language lessons in the primary school and defines the conditions to increase its efectiwness.